2005
DOI: 10.1063/1.1888566
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the nature of virtual amorphous silicon

Abstract: Virtual samples of approximations to real amorphous silicon, a-Si, have been prepared using several different processing routes. These include a fast quench from the melt followed by a long slow annealing period using molecular dynamics, a Reverse Monte Carlo approach, and an ab initio minimization. The characterization of these virtual a-Si samples includes a consideration of structural data (the radial distribution function, angular order, etc.), electronic properties (through the density of states), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The electronic density of states calculated with DFT/PBE for the lowest energy configuration gives a band gap that is a factor of 1.48 larger than that calculated for the crystal at the same level of theory. While the calculated band gaps are known to be too small in DFT/PBE, this ratio is in excellent agreement with the ratio of experimentally determined band gaps, 1.55 (see [38]). Two defect peaks are found in the gap, 0.09 and 0.15eV above the valence band edge, presumably corresponding to the coordination defects.…”
supporting
confidence: 84%
“…The electronic density of states calculated with DFT/PBE for the lowest energy configuration gives a band gap that is a factor of 1.48 larger than that calculated for the crystal at the same level of theory. While the calculated band gaps are known to be too small in DFT/PBE, this ratio is in excellent agreement with the ratio of experimentally determined band gaps, 1.55 (see [38]). Two defect peaks are found in the gap, 0.09 and 0.15eV above the valence band edge, presumably corresponding to the coordination defects.…”
supporting
confidence: 84%
“…In an SGMD simulation, the system undergoes an accelerated systematic motion, which is defined by the local averaging time, t L , while maintaining a desired temperature. Many applications have demonstrated that SGMD simulations have an enhanced conformational search ability (Choudhary & Clancy 2005a; 2005b; Lung et al 2001; Sheng et al 2010a; 2010b; Varady et al 2002; Wu & Wang 2000; 2001; Wu et al 2002). Shinoda and Mikami extended SGMD to the NPT ensemble (Shinoda & Mikami 2001) and later combined it with the rigid body dynamics (Shinoda & Mikami 2003).…”
Section: History Of the Sgmd And Sgld Methodsmentioning
confidence: 99%
“…The self-guided molecular dynamics (SGMD) (Wu & Wang 1998; 1999) and the self-guided Langevin dynamics (SGLD) (Wu & Brooks 2003; Wu & Brooks 2011a; 2011b) simulation methods were developed for an efficient conformational search and have found many applications to study rare events, such as protein folding (Lee & Chang 2010; Lee & Olson 2010; Wen et al 2004; Wen & Luo 2004; Wu & Sung 1999; Wu & Brooks 2004; Wu & Wang 2000; 2001; Wu et al 2002), and ligand binding (Lung et al 2001; Varady et al 2002; Yang et al 2004), docking (Chandrasekaran et al 2009), conformational transitions (Damjanovic et al 2009; Damjanovic et al 2008a; Damjanovic et al 2008b; Pendse et al 2010), crystallization (Abe & Jitsukawa 2009; Choudhary & Clancy 2005a; 2005b; Tsuru et al 2010; Wu & Wang 1999), and surface absorption (Sheng et al 2010a; 2010b)…”
Section: The Conformational Search Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common and simpler procedure for generating a-Si using MD simulations is by the quenching of l -Si [13,27,[47][48][49][50], which resembles the preparation of a-Si by pulsed energy melting techniques. Typical cooling rates used in this computational procedure are of the order of 10 13 − 10 14 K/s [13,27,47,48], while few studies have characterized samples generated with slower cooling rates [49][50][51]. These cooling rates are comparable (and some of them larger) to cooling rates experimentally achieved in pulsed energy melting techniques [4,6].…”
mentioning
confidence: 99%